2021
DOI: 10.1111/jgh.15580
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dapagliflozin on hepatic and visceral fat in type 2 diabetes patients with non‐alcoholic fatty liver disease

Abstract: Background and Aim: Sodium-glucose cotransporter 2 inhibitors have shown excellent results in glucose control in type 2 diabetes mellitus (T2DM) patients, while also promoting weight loss. These mechanisms may be beneficial in the treatment of non-alcoholic fatty liver disease (NAFLD). Our study aims to investigate the effect of dapagliflozin on hepatic and visceral fat contents and related biochemical markers in T2DM with NAFLD patients. Methods: This is a double-blinded placebo-controlled randomized, single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…In general, lifestyle modifications for weight reduction and treatment of extrahepatic comorbidities take precedence over direct NAFLD treatment. 8 , 9 , 10 Recently, anti‐diabetic drugs, such as glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) 11 , 12 , 13 and sodium/glucose cotransporter 2 inhibitors (SGLT2‐Is), 14 , 15 , 16 , 17 , 18 , 19 , 20 have been investigated as effective drugs for NAFLD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In general, lifestyle modifications for weight reduction and treatment of extrahepatic comorbidities take precedence over direct NAFLD treatment. 8 , 9 , 10 Recently, anti‐diabetic drugs, such as glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) 11 , 12 , 13 and sodium/glucose cotransporter 2 inhibitors (SGLT2‐Is), 14 , 15 , 16 , 17 , 18 , 19 , 20 have been investigated as effective drugs for NAFLD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of SGLT2 on adipokine levels was poorly explored in clinical trials with NAFLD patients. A study verified no significant differences in adiponectin and leptin levels in the dapagliflozin-treated group compared to the placebo group [ 157 ], whereas the lower serum level of high-molecular-weight adiponectin was correlated with an improved response to dapagliflozin in T2DM patients with NAFLD [ 156 ]. Altogether, SGLT2 inhibitors seem to be an interesting therapeutic option for T2DM patients with NAFLD, but clinicians need to consider their efficacy and safety when individualizing the treatment [ 156 ].…”
Section: Therapeutic Interventions and Modulation Of Adipokines’ Levelsmentioning
confidence: 99%
“…Since three studies included multiple dose groups of SGLT-2 inhibitors, these datasets were included in the meta-analysis as independent comparisons [22,23,25]. The studies included in the meta-analysis were published between 2012 and 2021, and performed in Japan [23][24][25][26][27][28][29], China [30], Thailand [35], the United Kingdom [22], Italy [31], Sweden [32], Germany [33], and the United States [34]. Various SGLT-2 inhibitors were used in these studies, such as dapagliflozin, tofogliflozin, luseogliflozin, ipragliflozin, empagliflozin, and canagliflozin.…”
Section: Study Characteristics and Data Qualitymentioning
confidence: 99%
“…Accordingly, it has been proposed that the benefits of SGLT-2 inhibitors on cardiorenal outcomes in patients with T2DM may be related to the increased plasma adiponectin following the treatment [21]. However, previous randomized controlled trials (RCTs) evaluating the effect of SGLT2 inhibitors on plasma level of adiponectin in patients with T2DM showed inconsistent results [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Although a previous meta-analysis suggested that SGLT-2 inhibitors were associated with an increment of plasma adiponectin [36] in T2DM patients, only ten studies published before 2018 were included, and the recent published RCTs were not included [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation